A Comparison of Clinical Outcomes Following Femoropopliteal Bypass or Plain Balloon Angioplasty with Selective Bare Metal Stenting in the Bypass Versus Angioplasty in Severe Ischaemia of the Limb (BASIL) Trial. (July 2019) - Meecham, Lewis; Bate, Gareth; Patel, Smitaa; Bradbury, Andrew W.
Abstract : Objective: To compare outcomes in patients with chronic limb threatening ischaemia (CLTI) due to femoropopliteal (FP), with or without infrapopliteal (IP), disease who underwent FP (vein or synthetic) open surgical bypass (OSB), or plain balloon angioplasty (PBA), with or without bare metal stenting (BMS), in the Bypass versus Angioplasty in Severe Ischaemia of the Limb (BASIL-1) trial. Methods: Data were extracted from BASIL-1 case record forms. Outcomes reported include immediate technical success, freedom from major adverse limb events (FF-MALE) and further re-intervention (FF-R), amputation free survival (AFS), overall survival (OS), and limb salvage (LS). Results: Patients underwent primary OSB ( n = 128; 89 vein, 39 synthetic) or primary PBA ( n = 183; six had BMS). Mean follow up was 46.2 and 43.6 months respectively. Patients were well matched at baseline except that PBA ± BMS patients were significantly more likely to be current smokers. There was no difference in overall or IP (runoff) Bollinger angiogram scores between groups. Immediate technical success was significantly higher for OSB (98% vs. 81%; p < .001). OSB was associated with a longer mean index hospital admission ( p = .001), but there was no difference in hospital days at 12 months. FF-MALE (hazard ratio [HR] 1.51; p = .04) and FF-R (HR 1.68; p = .02) but not AFS (HR 1.18; p = .4), OS (HR 1.14; p = .5), and LS (HR 1.09; p = .8) were significantly better after OSB. Conclusion: Although AFS, OS, and LS were similar in the two groups, OSB was associated with significantly fewer MALE and re-interventions. So, while PBA ± BMS may be a less resource intensive (expensive) and morbid option in the short term, this appears unlikely to be the case in the longer term. Present data add further weight to the argument that, where possible, patients presenting with CLTI due to FP disease should be offered OSB as their primary revascularisation procedure.